Competition between platform ecosystems: a longitudinal study of MOOC platforms - Rothe, Hannes; Täuscher, Karl; Basole, Rahul C. (Twenty-Sixth European Conference on Information Systems, 2018)
The last decade has seen a rise in software-based platforms that engender entirely new ecosystems. In newly emerging platform markets, platforms compete for partners and customers in a rapidly changing environment. Yet, extant research mostly studies platforms’ supply-side and demand-side strategies in relatively established platform markets. By combining a market-level and platform-level perspective, our research aims to develop a holistic understanding about the interdependencies between business model decisions, market evolution, and performance outcomes of platforms in emerging markets. We focus on the novel context of Massive Open Online Course (MOOC) platforms, analyzing longitudinal data for 35 MOOC platforms and their ecosystems. To account for the multi-level perspective, our research applies an innovative mixed-methods approach that combines qualitative methods with quantitative measures and visualizations derived from network analysis. Our findings suggest that platforms in new markets converge towards common business models as market leaders imitate the business model innovations of its smaller competitors to manifest their market position. Based on these analyses, we derive four propositions on how the dynamics of a platform’s business model and ecosystem position affect each other and the platform’s market performance.